2015
DOI: 10.1016/j.jbi.2015.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of UMLS terminologies to identify risk of heart disease using clinical notes

Abstract: The second track of the 2014 i2b2 challenge asked participants to automatically identify risk factors for heart disease among diabetic patients using natural language processing techniques for clinical notes. This paper describes a rule-based system developed using a combination of regular expressions, concepts from the Unified Medical Language System (UMLS), and freely-available resources from the community. With a performance (F1=90.7) that is significantly higher than the median (F1=87.20) and close to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…The team from The Ohio State University (Shivade et al, this issue), ranked 6 th , identified concepts in the training data, belonging to a variety of openly available terminologies. They used these concepts to trigger rules consisting of regular expressions and UMLS concepts.…”
Section: Submissionsmentioning
confidence: 99%
“…The team from The Ohio State University (Shivade et al, this issue), ranked 6 th , identified concepts in the training data, belonging to a variety of openly available terminologies. They used these concepts to trigger rules consisting of regular expressions and UMLS concepts.…”
Section: Submissionsmentioning
confidence: 99%
“…The study of Shivade et al [51] includes two strategies; first, a rule-based strategy that relies on information as the length of a string when it is a section heading, the usage of camel case, and the set of commonly used words that constitute a section heading. The second one is focused on implicit sections.…”
Section: Resultsmentioning
confidence: 99%
“…Dollah and Aono have introduced ontology-based classification approaches for biomedical abstract text classification [9]. Authors in [10][11][12][13] Medical documents have been utilized in different tasks such as analyzing Framingham risk score (FRF), assessing risk factors in diabetic patients, discriminating heart disease risk factors, and finding risk factors for heart disease patients [14]. In this paper, we employ ontology as a feature extraction approach to detect meaningful words and expressions for augmenting documents.…”
Section: Feature Extraction In Medical Document Classificationmentioning
confidence: 99%